SHARING SPACES BETWEEN MAJORITIES AND MINORITIES: Negotiations of Muslim Communities in North Sumatra in Shaping a New Multiculturalism from a Social Philosophy Perspective - Sahfutra, Suryo Adi; Supartiningsih, Supartiningsih; Utomo, Agus Himmawan (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
Multiculturalism often positions the majority group as the central axis in establishing the rules of sociality. This article examines how urban social spaces in North Sumatra serve as dynamic platforms for interactions among diverse ethnic, religious, and cultural groups, with the Muslim community as the dominant majority. Using a phenomenological approach, the study explores how social realities are constructed through intergroup interactions. Field data, analyzed hermeneutically within a qualitative philosophical framework, reveal that these social spaces function both as arenas of conflict and as catalysts for integration. The findings highlight the dual roles of social spaces in fostering cooperation and preserving diverse identities, conceptualized through the metaphors of a “symphony" and a “mosaic.” The “symphony” illustrates harmonious collaboration among groups, while the “mosaic” reflects the coexistence of distinct identities. These dynamics contribute to a distinctive model of multiculturalism in Indonesia, where conflict is integrated as part of the social fabric, fostering deeper social cohesion. This research provides valuable insights for global discourses on diversity management and conflict resolution, particularly in multicultural urban societies.